2021
DOI: 10.1021/acsnano.1c04499
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional 3D-Printed Wound Dressings

Abstract: Personalized wound dressings provide enhanced healing for different wound types; however multicomponent wound dressings with discretely controllable delivery of different biologically active agents are yet to be developed. Here we report 3D-printed multicomponent biocomposite hydrogel wound dressings that have been selectively loaded with small molecules, metal nanoparticles, and proteins for independently controlled release at the wound site. Hydrogel wound dressings carrying antibacterial silver nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 58 publications
0
106
0
1
Order By: Relevance
“…The release profile of the active ingredient was independently controlled by the number of filaments in the dressing. Compared to controls, in vivo wound dressing studies containing AgNP and VEGF demonstrated improvement in granulation tissue formation and differential levels of vascular density, the latter being influenced by the type of growth factor release profile (extended or short release profile) [137].…”
Section: Metalsmentioning
confidence: 91%
“…The release profile of the active ingredient was independently controlled by the number of filaments in the dressing. Compared to controls, in vivo wound dressing studies containing AgNP and VEGF demonstrated improvement in granulation tissue formation and differential levels of vascular density, the latter being influenced by the type of growth factor release profile (extended or short release profile) [137].…”
Section: Metalsmentioning
confidence: 91%
“…According to the shape of the wound, 3D printing can be used to prepare individualized patches conforming to the shape of the wound. Alizadehgiashi et al (2021) used cellulose nanocrystals and methyl acrylamide-chitosan as printing inks to prepare hydrogel patches with homogeneous composition and mesh structure by 3D printing for active substance delivery, which is not possible with conventional patches for their incompetent in reaching the deeper layers of the skin. The bulged microstructure on the surface of the patch can penetrate well into the deep part of the damaged skin, realizing the profound delivery of bioactive factors to promote skin repair.…”
Section: Structure Of Hydrogels For Wound Healingmentioning
confidence: 99%
“…A bacterial contagion is often assumed to be present when the pH of a wound shifts from acidic to alkaline values [ 276 ]. For regulated drug and wound therapy, Mirani et al used 4D bioprinting based on hydrogel dressings as drug-loaded and pH-reactant alginate scaffold arrays ( Figure 6 ) [ 298 ]. Based on pH-induced color change and swelling (pH level variation posed by the bacterial infection), this multifunctional dressing was capable of monitoring the infection level of the wound and antibiotic release at the wound site.…”
Section: Applications Of 4d Printed Hydrogelsmentioning
confidence: 99%